2009
DOI: 10.1101/gr.088922.108
|View full text |Cite
|
Sign up to set email alerts
|

Ride the wavelet: A multiscale analysis of genomic contexts flanking small insertions and deletions

Abstract: Recent studies have revealed that insertions and deletions (indels) are more different in their formation than previously assumed. What remains enigmatic is how the local DNA sequence context contributes to these differences. To investigate the relative impact of various molecular mechanisms to indel formation, we analyzed sequence contexts of indels in the non protein-or RNA-coding, nonrepetitive (NCNR) portion of the human genome. We considered small (#30-bp) indels occurring in the human lineage since its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Consistent with this view, Ball et al [2005] reported strong similarities between microinsertions and microdeletions in terms of the sequence characteristics and repetitivity of the flanking DNA sequence, the overrepresentation of motifs known to play a role in recombination, mutation, cleavage, and rearrangement, and the likely involvement of various types of repetitive sequence element in the mutational mechanism. Similar conclusions have been drawn from studies of microdeletions and microinsertions identified in an evolutionary context [Zhang and Gerstein, 2003; Taylor et al, 2004; Messer and Arndt, 2007; Tanay and Siggia, 2008; Kvikstad et al, 2009; Sjödin et al, 2010]. Taken together, these results are consistent with the view that microdeletions and microinsertions are generated by very similar sequence-directed molecular mechanisms.…”
Section: Microdeletions Microinsertions and Indelssupporting
confidence: 87%
“…Consistent with this view, Ball et al [2005] reported strong similarities between microinsertions and microdeletions in terms of the sequence characteristics and repetitivity of the flanking DNA sequence, the overrepresentation of motifs known to play a role in recombination, mutation, cleavage, and rearrangement, and the likely involvement of various types of repetitive sequence element in the mutational mechanism. Similar conclusions have been drawn from studies of microdeletions and microinsertions identified in an evolutionary context [Zhang and Gerstein, 2003; Taylor et al, 2004; Messer and Arndt, 2007; Tanay and Siggia, 2008; Kvikstad et al, 2009; Sjödin et al, 2010]. Taken together, these results are consistent with the view that microdeletions and microinsertions are generated by very similar sequence-directed molecular mechanisms.…”
Section: Microdeletions Microinsertions and Indelssupporting
confidence: 87%
“…Recent studies on the mechanisms of insertion, deletion, DNA repair, and replication (16,(34)(35)(36)(37)(38)(39) provide possible explanations for our observations. The generation of structural alteration (e.g., insertion or deletion) requires single-stranded and double-stranded breaks.…”
Section: Resultsmentioning
confidence: 62%
“…Although we observed more aneuploidy and small indel events than ever before, there were too few total events to perform the analyses possible in SNMs. Specifically, small indels showed a potential bias toward deletions and net loss of genic material, but it was impossible to clarify whether this bias was due to selection against strongly deleterious mutations or a true bias in the mechanisms that generate indels (59)(60)(61)(62)(63)(64). Lastly, measuring the individual fitness effects of each new mutation is also critical (65).…”
Section: Discussionmentioning
confidence: 99%